CSIG-15. SLFN5: A REPRESSOR OF INTERFERON-INDUCED SIGNALING THAT STIMULATES GLIOBLASTOMA CELL PROLIFERATION. SURVIVAL RESPONSES IN DIFFERENT XENOGRAFT GLIOBLASTOMA MOUSE MODELS. (5th November 2018) - D. Eckerdt, Frank; Fischietti, Mariafausta; Horbinski, Craig; James, C David; Platanias, Leonidas
Abstract: The Schlafen (SLFN) family of proteins are involved with essential cellular functions in normal as well as tumor biology. In our previously published work (Oncogene 2017;36:6006–6019) we showed that high-level expression of SLFN5, an IFN-regulated member of the SLFN protein family, was correlated with shorter overall survival in glioblastoma (GBM) patients and that SLFN5 is a contributor to the aggressive biology of GBM in stimulating the proliferation, motility and invasiveness of GBM cells, as indicated by the results of in vitro assays. In that study we had also found that type-I IFN treatment triggers SLFN5 interaction with STAT1, and this suppresses STAT1-mediated gene transcription. Thus, SLFN5 is a repressor of IFN-gene transcription, suggesting the existence of a feedback loop that may contribute to the suppression of antitumor immune response. Here, we have examined the engraftment and xenograft growth effects of U87 SLFN5 KO cells. Wild-type (wt) and KO cells were intracranially injected in athymic nu/nu mice as well as NSG-SGM3 mice: the former are T-cell deficient whereas the latter are deficient in T-, B-, and NK cells. Athymic and NSG-SGM3 mice injected with KO cells lived significantly longer than mice injected with wt cells: all two-way comparisons yielded log-rank p-values of 0.011 or less. Interestingly, the survival of NSG-SGM3 mice injected with KO cells was significantly reduced relative to athymic nu/nu mice injected with the same cells: p = 0.027. This differential response raises the possibility of a potential immunosuppressive effect of SLFN5 involving NK and B-cells. Immunohistochemical analysis of intracranial xenograft tumors for KO effects on proliferation, apoptosis, and immune cell infiltrates is ongoing, and will be presented at the meeting.